Geology and mine planning - Maturana-Bascope, M (Rhodes University, Faculty of Science, Department of Geology, 1983)
From introduction: This dissertation aims to review the main aspects involved in mine planning, in order to provide the geologists with the main criteria to obtain a preliminary estimate of the minability of an in situ orebody, and to make the geologists aware of the information they can contribute to the planning engineers. Furthermore, an understanding of the basic principles behind mine planning may help the exploration geologist to select more realistic targets of exploration.
Keywords: Geology; Mining geology; Geology, Economics